Hubungan Pemelihara Kucing dan Kejadian Toksoplasmosis pada Ibu Hamil Trimester 2 - Acivrida Mega Charisma; Nora Charissa Amelinda; Marsellyna Rahma Gantari; Alifia Febrianti; Niken Ayu A; Anastasia Junyantris Ebu; Moh. Bintang T. R; Fitrine Ekawasti (Calory Journal Medical Laboratory Journal, 2026)
Toxoplasmosis is caused by Toxoplasma gondii, a protozoa that is often found in cats as the definitive host. The infection can spread to humans through contact with cat feces or consumption of contaminated food and drinks. Pregnant women, especially in the second trimester, are at high risk of developing infections that can be transmitted to the fetus. Primary infections during pregnancy can lead to a variety of complications, including birth defects, and premature birth. The purpose of this study is to examine the relationship between cat ownership and the incidence of toxoplasmosis in pregnant women in the second trimester. This study is the result of a literature review with a literature search method conducted on the internet and scientific journals based on questions about the relationship between cat keepers and the incidence of toxoplasmosis in pregnant women in the 2nd trimester. According to the (WHO), the incidence ratio in 26 countries is based on concrete evidence. The three countries with the highest IgG seroprevalence according to data are Ethiopia (64.2%, 95%CI: 34.3–89.1), Gabon (56.7%, 54.4–59.0), and Brazil (53.8%, 39.3–68.0) but there are also three countries with the lowest IgG are Mexico (7.2%, 5.3–9.4), South Korea (2.1%, 0.6–4.3), and Canada (0.2%, 0.2–0.3). Meanwhile, the prevalence of toxoplasmosis in pregnant women in Indonesia ranged from 43% to 88% in 2014. Data shows that keeping cats as well as poor hygiene practices can increase the risk of toxoplasmosis infection in pregnant women.